Dampak International Financial Reporting Standard (IFRS) terhadap Laporan Keuangan Perusahaan di Indonesia - Evi Maulida Yanti; Ramzijah Ramzijah (Jurnal Ekobismen, 2023)
This study aims to explore information about the impact of international financial reporting standards on the financial statements of companies in Indonesia. This research method uses a Systematic Literature Review (SLR), which is a method for identifying and defining IFRS through philosophy based on previous studies. The results show that the application of international financial reporting standards (IFRS) in Indonesia has not been able to improve the quality of accounting information. The relevance of accounting earnings to investment decisions as reflected in stock prices does not increase significantly in the period after the adoption of IFRSKeywords: IFRS, company financial statements.